Deconstruction and the ethical in Asian thought - Wang, Youru (Routledge studies in Asian religion and philosophy, 2007)
The parallels between Derrida's deconstruction and certain strategies eschewing oppositional hierarchies in Asian thought have attracted attention from scholars of both Western and Asian philosophy.